DIGITALISASI UMKM KELURAHAN MENANGGAL MELALUI TIKTOK SEBAGAI MEDIA PROMOSI KREATIF - Rahmawati, Dea; Rachmawati, Farikha; Ahnaf, Muhammad; Setiyoso, Budiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Low digital literacy remains a major barrier for Micro, Small, and Medium Enterprises (MSMEs) in utilizing social media as a marketing strategy. This community service program aimed to enhance the digital promotion skills of MSME actors in Menanggal Subdistrict, Surabaya, through TikTok-based training. The program engaged 30 business owners from various sectors. The implementation method adopted a participatory action approach through door-to-door visits, supported by interactive material delivery, hands-on content creation practice, and evaluation using pre- and post-tests. The Wilcoxon analysis showed a significant increase in participants’ understanding, with the average score rising from 51.67 to 91. The training not only provided technical skills but also fostered awareness of the importance of adapting to digital trends. These results demonstrate that practical, context-based education effectively supports the digital transformation of MSMEs. The program also highlights the role of university students as agents of change in bridging the digital divide at the grassroots level. Sustainability was strengthened through the creation of an online communication group for continued mentoring and consultation. These findings serve as a replicable model of adaptive and participatory digital training to improve MSME competitiveness in the digital economy era. Keywords​: ​​Community Service, Digital Marketing, MSMEs Empowerment, TikTok